2021
DOI: 10.3390/genes12060808
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Characterization and Expression Profiling of myosin Family Genes in Sebastes schlegelii

Abstract: Myosins are important eukaryotic motor proteins that bind actin and utilize the energy of ATP hydrolysis to perform a broad range of functions such as muscle contraction, cell migration, cytokinesis, and intracellular trafficking. However, the characterization and function of myosin is poorly studied in teleost fish. In this study, we identified 60 myosin family genes in a marine teleost, black rockfish (Sebastes schlegelii), and further characterized their expression patterns. myosin showed divergent expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Here, S. schlegelii FGF genes showing a response to myoblast differentiation were selected to investigate the potential functions of FGF genes in muscle growth in vivo. Our current results show that all selected FGF genes were dynamically expressed during the muscle development of juvenile S.schlegelii (from 20 dpp to 90 dpp) ( Figure 4 B), among which, the expression levels of FGF10a , FGF19 , FGF6a , and FGF7 were found to significantly increase from 50 dpp to 75 dpp, corresponding to the periods during which the number and size of muscle fibers significantly increased [ 33 ], indicating their vital roles in contributing to the muscle growth.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Here, S. schlegelii FGF genes showing a response to myoblast differentiation were selected to investigate the potential functions of FGF genes in muscle growth in vivo. Our current results show that all selected FGF genes were dynamically expressed during the muscle development of juvenile S.schlegelii (from 20 dpp to 90 dpp) ( Figure 4 B), among which, the expression levels of FGF10a , FGF19 , FGF6a , and FGF7 were found to significantly increase from 50 dpp to 75 dpp, corresponding to the periods during which the number and size of muscle fibers significantly increased [ 33 ], indicating their vital roles in contributing to the muscle growth.…”
Section: Discussionmentioning
confidence: 93%
“…The eif5a1 gene was used as the reference gene for standardizing the expressions of genes under testing [ 68 ]. The qRT-PCR analysis was performed under conditions as described previously [ 33 ]. The relative expressions of tested genes were calculated using the 2 −ΔΔCt comparative Ct method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, this SNP was located within the MYH15 gene, which belongs to the myosin heavy chain gene family. Myosins are superfamily genes of eukaryotic motor proteins that bind actin and use ATP hydrolysis energy to contribute significantly to a wide range of biological processes, such as muscle contraction, cytokinesis, cell motility and contractility, and intracellular trafficking [ 33 ]. A previous meta-analysis of GWAS revealed that the MYH15 gene is listed as a plausible candidate gene for detecting pleiotropic polymorphisms for body height, reproduction, and fatness in beef cattle [ 34 ], as well as pleiotropic effects on body composition in sheep [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA extraction of intestines and livers was performed by TRIzol reagent (Invitrogen, Carlsbad, CA, United States) according to the protocols of our lab [ 40 ]. After removing genomic DNA by Dnase I (TaKaRa, Dalian, China), the quality and quantity of RNA were evaluated by 1.5% agarose gel electrophoresis and NanoPhotometer Pearl (Implen GmbH, Munich, Germany), respectively.…”
Section: Methodsmentioning
confidence: 99%